An isomerized alkyl side chain enables efficient nonfullerene organic photovoltaics with good tolerance to pre/post-treatments. (25th February 2021) - Han, Chenyu; Jiang, Huanxiang; Wang, Pengchao; Yu, Lu; Wang, Jianxiao; Han, Jianhua; Shen, Wenfei; Zheng, Nan; Wen, Shuguang; Li, Yonghai; Bao, Xichang
Abstract : An alkyl isomerization strategy is reported to finely modulate the crystallinity of nonfullerene acceptors as well as their photovoltaic responses to post-treatments. Abstract : The bulk-heterojunction (BHJ) blend plays an important role in determining the charge transport behavior and efficiency of organic solar cells. Side chain engineering has been recognized as one feasible way to tune BHJ networks. As a promising side chain species, the well-aligned alkyl chains could promote the ordered molecular assembly, but often induce inferior self-aggregated BHJ morphology ascribed to the overly strong crystallinity. Herein, we provide an isomerization strategy to modulate the crystallinity of an alkyl chain attached acceptor. The linear alkyl chain is isomerized to a branched structure with a bulky isopropyl terminal. As a consequence, the crystallinity of the acceptor is mildly reduced but the preferred molecular orientations, absorption and energy level properties are maintained. As for the as-cast devices, the isomerized iso-IDIC generates a better-developed BHJ morphology and a greater efficiency of 13.10% compared to the linear chain attached IDIC (12.37%). Impressively, the slightly decreased crystallinity of iso-IDIC reveals good tolerance to pre/post-treatments of the BHJ, with the thermal annealing delivering over 13.50% efficiency. However, the IDIC based devices produce negative response to the pre/post-treatments, ascribed to the seriously aggregated BHJ networks. Therefore, the BHJ should be carefully modulated and the isomerized side chain proposed here provides a promising approach to finely tune the acceptor crystallinity and the resulting morphology.